Earthquake Disaster Recovery: A Literature Review - Thohar, Amru ubaidillah; Cahyanti, Anindya disetya; Harianto, Maria kireina; Sucita, Ni Made dwiastini (Tarqabin Nusantara Group, 2024)
Earthquakes pose significant challenges as one of the most devastating natural disasters. Despite intensive efforts, deterministic prediction remains uncertain. According to statistics presented by the Centre for Research on the Epidemiology of Disasters (CRED) from 2000 to 2019, earthquakes caused the most significant damage among natural disasters, resulting in 58% of fatalities. Additionally, earthquakes rank second only to storms in terms of economic losses, averaging US32.7 billion annually. Effective disaster recovery management is crucial following major earthquakes. This literature review aims to evaluate public knowledge of post-earthquake recovery management. Through a systematic literature review methodology, relevant articles were identified using various academic databases including Google Scholar, Scopus, and Perplexity. Inclusion criteria encompassed articles addressing recovery strategies, interventions, challenges, and best practices following earthquakes. The review highlights pre-disaster activities, risk assessment, coordination, infrastructure recovery, decision-making, and post-disaster management phases. Overall, this review provides valuable information for policymakers to address post-earthquake disaster management in designing effective and holistic post-earthquake disaster management programs.